Effects of sponge iron dosage on nitrogen removal performance and microbial community structure in sequencing batch reactors. (January 2023) - Zhu, Hongjuan; Li, Wenxuan; Chen, Xinjuan; Mu, Hao; Hu, Kaiyao; Ren, Shuang; Peng, Yuzhuo; Zhao, Ruifeng; Wang, Yae
Graphical abstract: Highlights: Nitrogen was efficiently removed by bio-chemical reactions. The anaerobic-anoxic-aerobic microenvironment formed in BSIS. Denitrification bacteria enriched along with iron bacteria in BSIS. SI improved the denitrification ability and reactor stability. 90 g/L SI addition obviously improved the nitrogen removal rate of BSIS. Abstract: The application of sponge iron (SI) carriers can improve the biochemical treatment performance of sequencing batch reactors (SBR) during wastewater treatment. This study used SBR reactors to explore the effects of SI dosage on the nitrogen removal performance and reactor stability and microbial community structure under low temperature and ultra-low load. In contrast to conventional SBR, the average removal rate of total nitrogen (TN) in the biological sponge iron system (BSIS) was increased by 5.38 % for 45 g/L, 18.93 % for 90 g/L, and 13.52 % for 135 g/L, respectively. The nitrogen removal performance and reactor stability showed the best performance under the SI dosage of 90 g/L. The addition of SI formed the anaerobic-anoxic-aerobic microenvironments, which facilitate the propagation of denitrifying bacteria ( Saccharimonadales, Hydrogenophaga ) and iron bacteria ( Rhodoferax and Acinetobacter ) in the BSIS. This study provides a new insight on the application of SI in the wastewater treatment.